39 Getting it 'RIGHT'. (October 2018) - Kumar, J; O'Connor, C; Cronin, E; Caples, N; Asgedom, S; Owens, P; O'Callaghan, P; O'Dea, J
Abstract : Introduction: In Ireland about 90 000 patients are suffering from heart failure, with a further 10 000 being diagnosed every year. This places significant burden on hospital resources nationally, resulting in 2 31 042 use of bed days and a total cost of €277 million. As a result of Paradigm HF clinical trial Sacubitril/Valsartan combination was recommended for treatment in Heart Failure guideline in 2016. Since then there have been studies on the effect of Sacubitril/Valsartan on LV function which appears to be positive, but very little research done on the effect of this combination on right ventricular function. Due to the complex right ventricular anatomy, only a few echocardiographic parameters are reliable and easily obtainable. Methods: Retrospective cohort analyses was performed on patients with heart failure with reduced ejection fraction (HFrEF) attending the Heart failure clinic in University Hospital Waterford. Electronic and written patient records were sourced for patient level data. Echocardiographic parameters of right ventricular systolic function used were 1) tricuspid annular planar systolic excursion (TAPSE), 2) Tricuspid sub-annular diameter and 3) Right ventricular systolic pressure. Those taking sacubitril/valsartan 'ARNI group' (n=51) were compared with age matched controls (n=20) on maximal medical treatment not including sacubitril/valsartan ('standard treatment group'). Results: Of the 51 patients enrolled who were taking Sacubitril/Valsartan with one year of follow-up, complete data was available for 28 patients (17 male and 11 female). These were then compared with age-matched controls from the standard treatment group (n=20). Treatment with Sacubitril/Valsartan was associated with an increase of 22.6% (1.51 to 1.852) in TAPSE (Wilcoxon rank sum p≤0.00056), decrease in Tricuspid sub-annular diameter of 7.1% (4.22 to 3.92) (Wilcoxon rank sum p≤0.00014) and increase in Right ventricular systolic function of 22.5% which was statistically significant. Conclusions: From this study we found that treatment with Sacubitril/Valsartan significantly improves TAPSE, Tricuspid sub-annular diameter and systolic function of right ventricle.